Anti-TNF Therapy in Pregnant Women With Inflammatory Bowel Disease: Effects of Therapeutic Strategies on Disease Behavior and Birth Outcomes. Issue 1 (29th May 2019) - Julsgaard, Mette; Hvas, Christian L; Gearry, Richard B; Gibson, Peter R; Fallingborg, Jan; Sparrow, Miles P; Bibby, Bo M; Connell, William R; Brown, Steven J; Kamm, Michael A; Lawrance, Ian C; Vestergaard, Thea; et al.
Abstract : Discontinuation of anti-TNF before gestational week 30 did not increase the risk of relapse in the third trimester. Relapse and continuation of anti-TNF throughout pregnancy were each independently associated with lower birth weight, a marker associated with long-term adverse outcomes. Abstract: Background: Active inflammatory bowel disease (IBD) adversely affects pregnancy outcomes. Little is known about the risk of relapse after stopping anti–tumor necrosis factor (anti-TNF) treatment during pregnancy. We assessed the risk of relapse before delivery in women who discontinued anti-TNF treatment before gestational week (GW) 30, predictors of reduced infant birth weight, a marker associated with long-term adverse outcomes, and rates and satisfaction with counseling. Methods: Pregnant women with IBD receiving anti-TNF treatment were prospectively invited to participate in an electronic questionnaire carried out in 22 hospitals in Denmark, Australia, and New Zealand from 2011 to 2015. Risk estimates were calculated, and birth weight was investigated using t tests and linear regression. Results: Of 175 women invited, 153 (87%) responded. In women in remission, the relapse rate did not differ significantly between those who discontinued anti-TNF before GW 30 (1/46, 2%) compared with those who continued treatment (8/74, 11%; relative risk, 0.20; 95% confidence interval [CI], 0.02 to 1.56; P = 0.08). Relapse ( P = 0.001) and continuation of anti-TNF therapy after GW 30 ( P = 0.007) were independently associated with reduced mean birth weight by 367 g (95% CI, 145 to 589 g; relapse) and 274 g (95% CI, 77 to 471 g; anti-TNF exposure after GW 30). Of 134 (88%) women who received counseling, 116 (87%) were satisfied with the information provided. Conclusions: To minimize fetal exposure in women in remission, discontinuation of anti-TNF before GW 30 seems safe. Relapse and continuation of anti-TNF therapy after GW 30 were each independently associated with lower birth weight, although without an increased risk for birth weight <2500 g. Most women received and were satisfied with counseling. Video Abstract: